Brinquedoteca Universitária e a formação docente: apontamentos sob a ótica de estudantes de Pedagogia - LAMBERT, Wesley Santos (2023)
The university toy library is an important space in the academic environment, contributing substantially to teacher training and in an expanded way, it enables the experience of playfulness, interactions and games to the subjects who seek references in it. Immersion practices to aspects of play as a teaching and learning tool. In this sense, we aim in this work to analyze the contributions of the university toy library in the training of students of the Degree Course in Pedagogy of the University Campus of Altamira of the Federal University of Pará. In order to theoretical support, authors such as SANTOS (2000), CUNHA (2010), KISHIMOTO (2010), FORTUNA (2011), REIS; ARAÚJO; BATISTA (2018), SALAZAR (2019), among others, using Bardin's content analysis (1977) as a technique. The sources were the reports of experiences of the students of the Pedagogy class 2019 morning, produced during the supervised internship of pedagogy in non-school environments and the pedagogical projects of the toy library. The research found that the university toy library has a diversified and formative role, playing a relevant role in the training of academics, requiring visibility and valorization by the university.